Pengaruh Sikap Mengeluh dan Jenis Kelamin Terhadap Perilaku Komplain di Fakultas Ekonomi dan Bisnis Universitas Udayana Denpasar - Putra, Nyoman Cendana; Giantari, I Gusti Ayu Ketut (E-Jurnal Manajemen; Vol 3 No 9 (2014), 2014)
Consumer complaint behavior is actions undertaken as a result of his discontent towards the purchase. In the process of the lecture of the existence of the complaint. The purpose of this research was to test and analyze the effect of attitudes towards gender complaining and complaining behavior. This research was conducted at the Faculty of Economics and business at Udayana University Denpasar city. The number of samples as many as 100 people, taken by using purposive sampling technique. Methods of data collection the questionnaire and analysis techniques used was multiple linear regression. Based on the results of the analysis it was found that the attitude of positive and significant effect are complaining against the conduct complaint. Have a sense of the growing attitude of complaining then it will also improve the behavior of the complaint. Significant effect of gender behavior complaint, indicating that there is a direct relationship between the sexes with behavior complaints
Keywords: Attitude to complain; gender; behavior complaint